Chronic abuse: study of a series of cases occurring in childhood and adolescence - Lugão, Klisia Verona M.S.F.; Gonçalves, Gabriela E.; Gomes, Ivete M.; Silva, Viviane P.; Jacobson, Ludmilla S.V.; Cardoso, Claudete Aparecida A. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: world Health Organization considers sexual abuse one of the greatest health problems publishes. Such grievance reaches children and adolescents many times silently, and are practiced, usually by people linked directly to victims. objective: to describe the characteristics of chronic abuse in children and adolescents, identify vulnerability factors associated with the same and evaluate the outcome of cases attended. methods it is studying a series of 264 cases in 260 patients from zero to 18 years, victims of sexual violence, including 104 cases of chronic abuse, as outpatients Care for Children and Adolescents Victims of Violence (ACAVV), of Antonio Pedro University Hospital, at Universidade Federal Fluminense. Logistic regression models, single and multiple, were used in the statistical analysis, considering chronic abuse, the dependent variable. results: variables related to 104 cases of sexual abuse chronic were kids (46), residence of the victims (68) and family environment (75 cases). Although the prevalent female sex (91/104 cases), boys were three times more likely to suffer chronic abuse, and victims of other types of maltreatment twice as likely to suffer this kind of abuse, and manipulation of genitals four times more likely to happen compared to acute sexual abuse. Conclusion: characteristics of victims of chronic abuse were children, aged between six and 10 years and adolescents. The victims were abused within the family environment, where the majority occurred in the victim’s residence committed by fathers and stepfathers, associated with other types of maltreatment. Importantly, half of the victims had vaginal sex with their aggressors.